Navigating cyberspace: defending self-efficacy, empathy, and teacher support as protective factors against cyberbullying among Malaysian youths with visual impairments - Ooi, Pei Boon; Chan, Nee Nee; Ku, Wen Li; Ahrumugam, Priyadharshini; Wan Jaafar, Wan Marzuki; Choo, Woo Onn (SAGE Publications, 2025)
Introduction: The study investigates the cyberbullying prevalence rates of Malaysian youths with visual impairments from the roles of cyberbullying victims, perpetrators, and bystanders. Method: A cross-sectional approach was employed, involving 199 youths with visual impairments participating in braille, paper-and-pen, and VoiceOver surveys. Results: Defending self-efficacy, empathic self-efficacy, and teachers’ social support are negatively linked to cyberbullying experiences. Defending self-efficacy is also positively associated with social support from family, friends, and teachers. Social support from teachers emerged as a key mediator, explaining how defending and empathetic self-efficacy reduced cyberbullying experiences. Discussion: In this study, the prevalence of cyberbullying among Malaysian youths with visual impairments revealed that 50.2% acted as “cyber bystanders” (the highest among three roles), 47.2% experienced “cyber victimization,” and 10.6% were involved in “cyber perpetration.” The majority (94.0%) of the participants are Internet users, with 76.4% using the Internet almost daily. Defending and empathic self-efficacy and perceived social support from teachers acted as protective factors against cyberbullying experiences. Teachers’ social support bridges personal resilience (self-efficacy) and reduces cyberbullying. This discovery further emphasizes teachers’ supportive role in mitigating the effect of cyberbullying. Overall, these findings contribute valuable knowledge to creating targeted interventions and support systems for visually impaired youths facing cyberbullying challenges. Implication for Practitioners: The findings underscore the crucial role of defending self-efficacy and teachers’ support in mitigating cyberbullying experiences among youths with visual impairments. Consequently, educational initiatives and interventions are imperative to raise awareness and strengthen the sense of self-efficacy among youths with visual impairments. Additionally, fostering a supportive environment contributes to the mental and emotional well-being of youths with visual impairments.